Effectiveness Comparison of Extracorporeal Shock Wave Therapy and Conventional Physical Therapy Modalities in Primary Knee Osteoarthritis - Yaşar Arslan; Ayhan Kul (Galenos Yayinevi, 2022)
Objective:In this study, it was aimed to compare the effects of radial-extracorporeal shockwave treatment (r-ESWT) and conventional physical therapy (PT) modalities treatments on pain, joint range of motion (ROM), functional status and walking speed in patients with primary knee osteoarthritis (KOA).Materials and Methods:A total of 51 patients (26 patients in the ESWT group and 25 patients in the combined PT group) diagnosed with stage 2 or stage 3 primary KOA according to the Kellgren-Lawrence staging were included in the study. ESWT protocol of 2.0 bar, 0.25 mJ/mm2 , and ten beats/sec frequency was used once a week for a total of three sessions. In the PT group, hot-pack 30 min/day, transcutaneous electrical nerve stimulation 30 min/day, and ultrasound 10 min/day were performed as a combination therapy for five sessions a week and in a total of three weeks. Besides, a therapeutic home exercise program was administered to both groups. The groups were assessed on days 0, 10, and 21 using the parameters of visual analog scale (VAS), Western Ontario McMaster Universities Osteoarthritis index (WOMAC), joint ROM measurements, and the Timed "Up & Go" (TUG) test.Results:No statistically significant differences were determined between the groups regarding the pretreatment and 10-day and 21-day posttreatment scores, VAS, WOMAC, joint ROM, and TUG parameters (p>0.05). In intra-group evaluations, statistically significant improvements were determined when the 10-day and 21-day values of VAS, WOMAC, joint ROM, and TUG parameters were compared to the pretreatment values (p<0.05).Conclusion:r-ESWT and conventional PT were determined to have similar effects on primary KOA treatment. However, further and comprehensive studies are needed to reach more precise and accurate results.